2000
DOI: 10.1002/(sici)1097-4628(20000103)75:1<78::aid-app9>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state polymerization and bulk crystallization behavior of poly(ethylene terephthalate) (PET)

Abstract: The main variables involved in solid-state polymerization of PET homopolymers, originally with molecular weight within the commercial range, were sequentially studied to determine their influence in polymerized products. These variables were precursor crystallinity, catalyst, and time and reaction temperature. An increasing molecular weight sequence was then used to study the bulk crystallization behavior with Avrami analyses. It was determined that thermal conditions at dissolution affect the prereaction morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…According to this assumption, if PET pellets are highly crystallized, the effective concentrations of end groups increase because of the concentration effect during crystallization. Medellin-Rodriguez et al 26 reported that high crystallinity sometimes favored high SSP rates for PET samples that were specially prepared by precipitation in a solvent to obtain high surface areas in the precursors. These contrary effects of crystallinity can be understood with respect to the SSP kinetic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…According to this assumption, if PET pellets are highly crystallized, the effective concentrations of end groups increase because of the concentration effect during crystallization. Medellin-Rodriguez et al 26 reported that high crystallinity sometimes favored high SSP rates for PET samples that were specially prepared by precipitation in a solvent to obtain high surface areas in the precursors. These contrary effects of crystallinity can be understood with respect to the SSP kinetic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The precursors were heated at 140 • C for 2 h prior to the SSP process for the following purposes. [9][10][11] The water molecule remaining in the sample would cause degradation of PET during the reaction, so the samples must be dried vigorously. Moreover, by the crystallization of PET during the heating process, the reactive chain ends and catalysts are considered to be concentrated into the amorphous region, which is necessary for the progress of SSP.…”
Section: Preparation Of Nanocompositesmentioning
confidence: 99%
“…A solid-state polymerization (SSP) process can be applied to increase the average molecular weight of PET without being affected by the viscosity of the reactants. [9][10][11] In the SSP process, the crystallized PET prepolymer is heated at a temperature below the crystalline melting point (T m ) but well-above the glass transition temperature (T g ) under a flow of inert gas or under vacuum. The hydroxyethyl end groups of the PET prepolymer are considered to be concentrated into the amorphous region during the crystallization process.…”
mentioning
confidence: 99%
“…Crystallization in step-growth polymers such as polyesters and nylons is known to assist their subsequent solid-state polymerization because exclusion of reactive end-groups from crystalline domains enhances their effective concentration in the amorphous domains [14,15]. However, the condensation reaction between the last fraction of end-groups may be hindered by crystallization [16,17].…”
Section: Tuning Polymer Crystallization For Propertiesmentioning
confidence: 99%